2019
DOI: 10.2514/1.j057249
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Transition Models for High-Angle-of-Attack Behavior

Abstract: This paper considers transition modeling for the flow over small unmanned aerial vehicles with a span of around 1 m. Such flows are characterized by very low values of turbulent intensity and the main cause for transition corresponds to flow separation. Four different turbulence models for low Reynolds number flow are compared with the experimental data for a NACA 0018 airfoil over a range of 2D as well as 3D conditions. The turbulence models under consideration are Menter's k − ω SST model with Wilcox's low-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Therefore, results on the suction side suggest that with increasing Reynolds number and angle of attack, the laminar separation bubble propagates towards the leading edge causing early transition and reattachment at some instances. However, with an increasing angle of attack, the separation point moves downstream on the pressure side [38]. Majority of the cases, bubbles are produced at both sides of the airfoil for Re = 1.7 × 10 5 except α = 3 o (Figure 7(h)).…”
Section: Mean Aerodynamic Characteristicsmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, results on the suction side suggest that with increasing Reynolds number and angle of attack, the laminar separation bubble propagates towards the leading edge causing early transition and reattachment at some instances. However, with an increasing angle of attack, the separation point moves downstream on the pressure side [38]. Majority of the cases, bubbles are produced at both sides of the airfoil for Re = 1.7 × 10 5 except α = 3 o (Figure 7(h)).…”
Section: Mean Aerodynamic Characteristicsmentioning
confidence: 95%
“…This model is not depending on nonlocal terms and the intermittency is modified to allow better prediction of separation-induced transition [26,32,36]. Additionally, the model predicts the formation and structure of the separated bubble well [37][38][39]. Above all, the model is mostly used for external flow measurements at relatively high Reynolds number (Re ≈ 10 6 ) and finite low Reynolds number [28].…”
Section: Introductionmentioning
confidence: 99%
“…The latter assures that the model captures strong variations of the turbulent intensity, that may occur due to turbulence decay, the influence of the free-stream and the pressure gradient [22]. This model was chosen over other transitional models based on a comperative study with experimental data for high angle of attack behavior [36].…”
Section: Computational Fluid Dynamicsmentioning
confidence: 99%
“…In the last couple of decades, a number of turbulence models have been developed that attempt to model the transition phenomena that are attributed to low Reynolds number flow. Here Menter et al's γ − Re θ model [22] is used based on a comparative study of transitional turbulence models [36]. It results in deviations of CL and CD up to 10% for the investigated conditions near the stall angle.…”
Section: Introductionmentioning
confidence: 99%
“…The prediction was close to the experimental results for = 0.3 × 10 6 presented in [5,6,12], but was not satisfactory for = 0.7 × 10 6 . In a recent study [13], a comparative analysis of transition turbulence models was carried out with the objective of capturing aerodynamic static hysteresis. It was shown that the and -turbulence models predict the laminar bubble on the top branch rather well at = 0.3 × 10 6 , giving a small overshoot in max , but they are completely unable to predict the lower branch of the static aerodynamic hysteresis with fully developed flow separation.…”
Section: Introductionmentioning
confidence: 99%